Risk factors associated with asthma, atopic dermatitis and rhinoconjunctivitis in a rural Senegalese cohort - Herrant, Magali (Allergy Asthma Clin Immunol, 2015)
BACKGROUND: The World Allergy Organization estimates that 40 % of the world’s population is affected by allergic diseases. The International Study of Asthma and Allergies in Childhood has completed Phase III and it has now become clear that these diseases have increased in developing countries, especially Africa, where prevalence rates were formerly low. Despite an increase in studies in Africa, few sub-Saharan West African countries are represented; the focus has remained on urban populations and little attention has been paid to rural sub-Saharan Africa. METHODS: We performed an allergy survey in a birth cohort of children aged less than 15 years in rural Senegal and implemented an ISAAC questionnaire. We carried out a complete blood count and serological analyses for IgE levels against common allergens and mosquito saliva. RESULTS: The prevalence rates of asthma, rhinoconjunctivitis (RC) and atopic dermatitis (AD) were 12.8, 12.5 and 12.2 % respectively. Specific IgE (sIgE) levels against mosquito spp. salivary gland antigens were significantly associated with AD; sIgE levels against selected true grasses (Poaceae) were significantly associated with RC. sIgE levels against house dust mite spp. were not associated with asthma, but were significantly correlated with mosquito IgE levels. Such cross-reactivity may blur the association between HDM sIgE and asthma. Consumption of seafood, storing whey cream, using plant fibre bedding and presence of carpet were significantly associated with increased risk of RC. The association of seafood may be the result of histamine intoxication from molluscs prepared by putrefaction. Cat presence and dog contact were associated with increased risk of asthma. Cow contact was associated with increased risk of AD. CONCLUSIONS: Our allergy study in rural West Africa revealed lower prevalence rates than the majority of African urban settings. Although several associated known risk factors were identified, there were associations specific to the region. The identification of probable artefactual dietary phenomena is a challenge for robust diagnosis of allergic disease. The association AD with mosquito saliva, a common allergen in rural settings, warrants specific attention. Further studies in rural Africa are needed to address the aetiology of allergy in a non-urban environment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13223-015-0090-0) contains supplementary material, which is available to authorized users.